Oblicz wartości liczbowe wyrażeń
a) 2(x2 – 4x + 5) – 1/ 3 (6x2 – 9x + 15) dla x = −1,4
b) y(2xy + 3x) − x(3y2 + 3y − x) dla x = 10, y = −0,6

Wiem, że ma wyjść
a) 12, b) 96,4


Odpowiedź :

Odpowiedź:

a)

2(x² - 4x + 5) - 1/3(6x² - 9x + 15) = 2x² - 8x + 10 - 6/3x²+ 9/3x - 15/3 =

= 2x² - 8x + 10 - 2x²+ 3x - 5 = - 5x + 5 = - 5 * (- 1,4) + 5 = 7 + 5 = 12

b)

y(2xy + 3x) - x(3y² + 3y - x) = 2xy² + 3xy - 3xy² - 3xy + x² =

= - xy² + x² = - 10 * (- 0,6)² + 10² = - 10 * 0,36 + 100 = - 3,6 + 100 = 96,4